INDIRECT REGENERATION FROM LEAF SEGMENTS FOR MASS PROPAGATION OF WITHANIA SOMNIFERA : AN ENDANGERED MEDICINAL PLANT - NISHESH SHARMA; EAPEN P KOSHY; MANJUL DHIMAN (International Journal of Pharma and Bio Sciences, 2014)
Withania somnifera, is an important medicinal plant known for its numerous traditional and medicinal uses. Low rate of germination in nature, poor seed viability and unrestricted collection from natural habitat have rendered the plant endangered. Hence, efforts are needed for conservation of this important medicinal plant. Present study has been carried out with an objective of developing a rapid and efficient protocol for mass propagation and conservation of the species. Callus development from leaf segments was achieved onto MS medium containing (2-10µM) NAA and (2-4µM)Kn or (2-10µM)IAA and (2-10µM)BAP. However, only the callus obtained from MS+IAA+BAP exhibited regeneration of shoot buds. Regenerated shoots were proliferated onto MS+BAP, with 11.04±0.20 average and 16 number of maximum shoots onto MS+10µM BAP. Elongated shoots were rooted onto ½ MS+IBA. Around 86.4% cultures were successfully rooted onto ½ MS+10µM IBA. Regenerated plants were acclimatized and about 82.4% plants survived during field transfer.